2007
DOI: 10.1159/000100870
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pioglitazone, a Peroxisome Proliferator-Activated Receptor Gamma Agonist, on Ischemia-Reperfusion Injury in Rats

Abstract: Two groups of rats were used to examine the effect of pioglitazone, a peroxisome proliferator-activated receptor γ (PPARγ) agonist, on rat hearts using an in vivo model of ischemia-reperfusion (I/R) to elucidate potential mechanisms. One group was the 30-min reperfusion group, which was further subdivided into sham (n = 5), vehicle (n = 6) and pioglitazone (3 mg·kg–1, n = 7) treatment groups with 30 min ischemia followed by 30 min reperfusion to detect data related to cardiac function and the area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
(24 reference statements)
1
22
0
Order By: Relevance
“…cao et al reported that there was high expression of the metabolic glutamic acid receptor mGlur1α on days 1 and 7 in rats exposed to ultrasound at 8 Hz 130 dB 2 h/day. The expression of mGlur1α was found to return to normal levels on day 14 (17). This suggests that notable changes occur in hippocampal Glu and its receptor upon exposure to infrasound at 8 Hz 120-130 dB applied daily for 2 h. regarding the effect of 8 Hz 130 dB infrasound on the increase in ca 2+ concentration, it was demonstrated that not only the ion glutamic acid receptor (iGlur), but also the metabolic glutamic acid receptor (mGlur), participated in its increase.…”
Section: Discussion Dynamic Changes In Camentioning
confidence: 98%
See 1 more Smart Citation
“…cao et al reported that there was high expression of the metabolic glutamic acid receptor mGlur1α on days 1 and 7 in rats exposed to ultrasound at 8 Hz 130 dB 2 h/day. The expression of mGlur1α was found to return to normal levels on day 14 (17). This suggests that notable changes occur in hippocampal Glu and its receptor upon exposure to infrasound at 8 Hz 120-130 dB applied daily for 2 h. regarding the effect of 8 Hz 130 dB infrasound on the increase in ca 2+ concentration, it was demonstrated that not only the ion glutamic acid receptor (iGlur), but also the metabolic glutamic acid receptor (mGlur), participated in its increase.…”
Section: Discussion Dynamic Changes In Camentioning
confidence: 98%
“…in this case, the effect on the increase in ca 2+ concentration was mainly mediated by mGlur1. infrasound at 8 Hz 130 dB was found to have an inhibitory effect on nMdar1 and mGlur1 expression on day 14; this coincided with a ca 2+ overload symptom, accompanying distinct damage in the ultramicroscopic structure of the cells, such as mitochondrial swelling and pyknosis (1,17). This indicates that the effect of 8 Hz 130 dB infrasound on day 14 directly resulted in damage to the structure of the cell membrane and the opening of various types of calcium channels, thus enabling extracellular ca 2+ to flow inwards and Ca…”
Section: Discussion Dynamic Changes In Camentioning
confidence: 98%
“…In models of diabetes mellitus and cardiovascular disease, activation of PPAR-␥ has been shown to restore vascular structure and correct endothelial dysfunction, [17][18][19] resulting in a reduction in the elevated blood pressure associated with hypertensive conditions. 20 -22 In the present study, administration of the PPAR-␥ agonist rosiglitazone to RUPP rats ameliorated both hypertension and endothelial dysfunction via a HO-1-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence indicates that apoptosis is a significant contributor to myocardial cell death after I/R, particularly during the early stages (1). Studies suggest that targeting the reperfusion-induced apoptotic component of cell death can affect the apoptotic and necrotic components of cell death, the consequences of which are a reduction in infarct size and improved contractile function.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that the peroxisome proliferator-activated receptor (PPAR) γ agonist, pioglitazone (PIO), may protect the heart from I/R injury; the protective effect is likely to occur by inhibiting cardiomyocyte apoptosis (1). PPARs are nuclear hormone receptors that stimulate transcription of specific genes by binding to specific DNA sequences after activation by an appropriate ligand.…”
Section: Introductionmentioning
confidence: 99%